Implementasi Strategi Pembelajaran Menggali Pikiran Ingin Tahu Terhadap Keaktifan Belajar Siswa - Basir, Zhafira; Aminullah; Sabriadi (Sipakatau: Jurnal Pendidikan dan Kebudayaan, 2024)
This study evaluates the "Exploring Curious Minds" learning strategy in Islamic Religious Education (PAI) at SMP Negeri 3 Palakka. Using qualitative methods, it assesses the strategy's effectiveness in promoting active learning and identifies supporting and inhibiting factors. The strategy involves encouraging student responses, accommodating answers, and using questions to connect with lesson material. However, student participation remained low, with limited question-asking and opinion-sharing. Supporting factors include teacher involvement, adequate facilities, and student interest. Inhibiting factors comprise teachers often skipping the question composition step, lack of student interest, fear of expressing opinions, and environmental disturbances.While the strategy shows potential, its implementation faced challenges in achieving desired student engagement levels. The study highlights the need to address both teacher and student-related factors to enhance its effectiveness. Data collection involved observation, interviews, and documentation, with analysis including data reduction, presentation, conclusion drawing, and verification. The research employed an Islamic education approach to examine the strategy's impact on active learning in PAI subjects. The findings underscore the importance of overcoming implementation barriers to fully realize the strategy's potential in fostering active learning in Islamic religious education at the school.